381 Role of CT scans of abdomen and pelvis in management of patients with immunotherapy-induced colitis. (9th November 2020) - Rovira, Juan Ibarra; Vikram, Raghunandan; Thirumurthi, Selvi; Yilmaz, Bulent; Lin, Heather; Akhmedzhanov, Fechukwu; Hong, David; Zarifa, Abdulrazzak; Tagart, Melissa; Meric-Bernstam, Funda; Naing, Aung
Abstract : Background: Colitis is one of the most common immune-related adverse event in patients who receive immune checkpoint inhibitors targeting cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death-1 (PD-1). Although radiographic changes are reported on computed tomography such as mild diffuse bowel thickening or segmental colitis, the utility of CT in diagnosis of patients with suspected immune-related colitis is not well studied. Methods: CT scans of the abdomen and pelvis of 34 patients on immunotherapy with a clinical diagnosis of immunotherapy induced colitis and 19 patients receiving immunotherapy without clinical symptoms of colitis (control) were enrolled in this retrospective study. Segments of the colon (rectum, sigmoid, descending, transverse, ascending and cecum) were assessed independently by two fellowship trained abdominal imaging specialists with 7 and 13 years' experience who were blinded to the clinical diagnosis. Each segment was assessed for mucosal enhancement, wall thickening, distension, peri-serosal fat stranding. Any disagreements were resolved in consensus. The degree of distension and the spurious assignment of wall thickening were the most common causes for disagreement. The presence of any of the signs was considered as radiographic evidence of colitis. Results: CT evidence of colitis was seen in 16 of 34 patients with symptoms of colitis. 7 of 19 patients who did not have symptoms of colitis showed signs of colitis on CT. The sensitivity, specificity, Positive Predictive Value and Negative Predictive Value for colitis on CT is 47%, 63.2%, 69.5% and 40%, respectively. Conclusions: CT has a low sensitivity, specificity and negative predictive value for the diagnosis of immunotherapy-induced colitis. CT has no role in the diagnosis of patients suspected of having uncomplicated immune-related colitis and should not be used routinely for management. Trial Registration: This protocol is not registered on clinicaltrials.gov. Ethics Approval: This protocol was IRB approved on: 11/16/2015 - IRB 4 Chair Designee FWA #: 00000363 OHRP IRB Registration Number: IRB 4 IRB00005015 Consent: This protocol utilizes an IRB approved waiver of consent.